Recent Trends in the Study of Medieval Canonizations - Katajala-Peltomaa, Sari (History compass, 2010)
Canonization processes, inquiries into a putative saint's life, merits and miracles, are rich sources for the study of lived experiences as well as religious practices of lay Christians. Studies of this field have multiplied during the 1990s and 2000s; the focus had shifted from overall categorizations and comparison of various processes to a narrower but nuanced perspective; qualitative close reading of the depositions is an important method of analysis. Currently, social history approach, everyday life, family and gender, as well as local interaction and political motivation behind the practicalities of the proceedings are pre-eminent themes in the study of medieval canonizations.